Lipid lowering drugs prescription and the risk of peripheral neuropathy: an exploratory case-control study using automated databases. Issue 12 (16th November 2004) - Corrao, Giovanni; Zambon, Antonella; Bertù, Lorenza; Botteri, Edoardo; Leoni, Olivia; Contiero, Paolo
Abstract : Study objective: Although lipid lowering drugs are effective in preventing morbidity and mortality from cardiovascular events, the extent of their adverse effects is not clear. This study explored the association between prescription of lipid lowering drugs and the risk of peripheral neuropathy. Design: A population based case-control study was carried out by linkage of several automated databases. Setting: Resident population of a northern Italian Province aged 40 years or more. Participants: Cases were patients discharged for peripheral neuropathy in 1998–1999. For each case up to 20 controls were randomly selected among those eligible. Altogether 2040 case patients and 36 041 controls were included in the study. Exposure ascertainment: Prescription drug database was used to assess exposure to lipid lowering drugs at any time in the one year period preceding the index date. Analysis: Conditional logistic regression model for matched data was used to estimate the risk of peripheral neuropathy associated with exposure to statins, fibrates, and other lipid lowering drugs. Main results: Weak but significant effects of lipid lowering drugs as a whole (matched odds ratio: 1.27; 95% confidence intervals: 1.05 to 1.55), statins (1.19; 1.00 to 1.40), and fibrates (1.49; 1.03 to 2.17) were observed. Significant linear trends towards increased risk at increased exposure to both statins and fibrates were observed. Conclusions: The use of both statins and fibrates was associated with the risk of peripheral neuropathy. The primary purpose of this exploratory study is signal generation. This requires further investigations to evaluate the causal role of lipid lowering drugs on the onset of peripheral neuropathy.